2004
DOI: 10.1152/japplphysiol.00465.2004
|View full text |Cite
|
Sign up to set email alerts
|

Regional hemodynamics during postexercise hypotension. I. Splanchnic and renal circulations

Abstract: Moderate exercise elicits a relative postexercise hypotension that is caused by an increase in systemic vascular conductance. Previous studies have shown that skeletal muscle vascular conductance is increased postexercise. It is unclear whether these hemodynamic changes are limited to skeletal muscle vascular beds. The aim of this study was to determine whether the splanchnic and/or renal vascular beds also contribute to the rise in systemic vascular conductance during postexercise hypotension. A companion stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 37 publications
4
42
1
4
Order By: Relevance
“…This underscores the possibility that systemic mechanisms, such as sympathetic decrease, opioid release, and thermoregulation, play a role. Since postexercise blood flow was measured in an inactive region and postexercise vasodilation is known to be more pronounced in exercised muscle (56), this response might have been even greater if the measurements had been taken on the leg.…”
Section: Discussionmentioning
confidence: 99%
“…This underscores the possibility that systemic mechanisms, such as sympathetic decrease, opioid release, and thermoregulation, play a role. Since postexercise blood flow was measured in an inactive region and postexercise vasodilation is known to be more pronounced in exercised muscle (56), this response might have been even greater if the measurements had been taken on the leg.…”
Section: Discussionmentioning
confidence: 99%
“…Franklin et al 57 observed that thermoregulation is another factor that could be associated with PEH. Nevertheless, a few studies suggest that thermoregulation 7 and splenic 58 , cutaneous 59 and cerebral 60 circulation contribute very little to PEH. Finally, another mechanism that might influence PEH is baroreflex function, which seems to increase after an exercise session 61,62 .…”
Section: Anunciação and Polito Post-exercise Hypotension In Hypertensivmentioning
confidence: 99%
“…After exercise, blood pressure (BP) falls below pre-exercise levels (Brandao Rondon et al 2002;Forjaz et al 1998Forjaz et al , 2004Halliwill et al 1996;Hayes et al 2000;Jones et al 2007;Pescatello et al 2004a;Pricher et al 2004;Queiroz et al 2009;Raine et al 2001;Rezk et al 2006;Senitko et al 2002;Takahashi et al 2000). On the other hand, heart rate (HR) persists elevated for many minutes or hours after exercise (Dujic et al 2006;Forjaz et al 1998Forjaz et al , 2004Heffernan et al 2006;Kannankeril et al 2004;Mourot et al 2004;Parekh and Lee 2005;Queiroz et al 2009;Rezk et al 2006;Savin et al 1982;Seiler et al 2007).…”
Section: Introductionmentioning
confidence: 99%